KONSEP SANGKOLAN: PEMETAAN PRAKTIK HIBAH DAN WARIS BERDASARKAN KAJIAN HUKUM ISLAM PADA KALANGAN PETANI - Nasrullah, Achmad Muzammil Alfan (El-Waroqoh : Jurnal Ushuluddin dan Filsafat, 2024)
This study aims to understand the concept of sangkolan from the perspective of Islamic law among farmers in Preng Ampel village, Pamekasan Regency. This research uses a qualitative approach with a case study method. The data sources used are local community leaders, religious figures, and residents. Data collection techniques include interviews and observations. The data analysis used is interactive analysis. The results of the study indicate that sangkolan is a practice of giving valuable assets from parents to their children or other family members who have a blood relationship. Based on Islamic law, sangkolan can be categorized as a practice of hibah (gifts) or inheritance, depending on the method of distribution. Therefore, sangkolan is fundamentally not in conflict with Islamic law as long as it is implemented correctly. The overlapping of the concepts of sangkolan with hibah and inheritance has been occurring due to several factors that require guidance from religious and community leaders through educational programs and equitable dissemination of understanding.